Note—A Simplified Expression for the Efficient Frontier in Mean-Variance Portfolio Analysis - Buser, Stephen A. (Management Science, 1977)
The identification of an important but previously overlooked technical property of minimum-variance portfolios greatly simplifies both the derivation of and the expression for the efficient frontier in mean-variance portfolio analysis. These simplifications permit a corresponding reduction in the analytics required to examine and to interpret essential properties of the model including comparative-static results and mutual-fund theorems.